Multipotent mesenchymal stromal cells in kidney transplant recipients: The next big thing?. (January 2021) - Sergeant, Elien; Buysse, Malicorne; Devos, Timothy; Sprangers, Ben
Abstract: Bone marrow-derived multipotent mesenchymal stromal cells (BM-MSCs) are non-haematopoietic cells present in the bone marrow stroma. They have the potential to modulate immune responses and exhibit a capacity to promote immune tolerance. Although the efficacy of immunosuppressive drugs has improved significantly, thereby ameliorating renal graft outcome, the use of these drugs still carries an increased risk of malignancies and opportunistic infections, and sometimes fail to prevent chronic allograft rejection or recurrence of the original kidney disease. As such, there is strong interest in ways to induce immune tolerance and thereby tempering or avoiding conventional immunosuppressive drugs. Cellular immunomodulation by MSCs can create a new way to induce transplant tolerance. This review will give a critical overview of the use of BM-MSCs as a cell-based immunosuppressive therapy in kidney transplant recipients. In vitro studies revealed several mechanisms that can clarify the immunomodulatory potential of BM-MSCs. Several clinical studies showed that BM-MSCs can modulate T-cell proliferation and can alter the ratio of T-cell subsets, favoring immune tolerance. However, this immunomodulation was often not associated with better clinical outcome during follow-up when compared to control groups. Some clinical studies found that BM-MSCs allow a reduction in dose of conventional immunosuppressive drugs and prevent acute graft dysfunction. Most clinical studies emphasized that BM-MSC infusion was safe. This review suggests that the use of BM-MSCs as cell-based immunosuppression therapy in kidney transplant recipients has potential, however some caution regarding their clinical use is appropriate. Mechanisms by which BM-MSCs induce transplant tolerance and factors that can alter their functionality need to be analyzed in more detail before clinical use.